Matrix metalloproteinases in nephrotic syndrome; a vital but obscure field of research - Souparnika Sreelatha; Benedicta D'souza; Vivian D'souza (Journal of Nephropathology, 2019)
Context: Matrix metalloproteinases (MMPs) are involved in the remodelling of the glomerular basement membrane (GBM) by tightly regulating the metabolism of extracellular matrix (ECM) of the GBM. Evidence Acquisitions: Directory of Open Access Journals (DOAJ), Google Scholar, PubMed, EBSCO, Scopus and Web of Science have been searched. Results: Gelatinases (MMP-2 and MMP-9) are mainly found involved in the remodelling of GBM and therefore this review focuses on these two MMPs and their action in nephrotic syndrome (NS), which is a protein losing enteropathy occurring due to the loss of integrity of GBM. In addition to the blood corpuscles, glomerular epithelial cells and mesangium are also expressing MMPs, and various cytokines and growth factors are involved in addition to tissue inhibitors of metalloproteinases (TIMPs) in regulating the metabolism of ECM via MMPs. While examining the results of MMP activity and expression in NS, except diabetic nephropathy (DN), membranoproliferative glomerulonephritis (MPGN) and hereditary NS where there was a clear down-regulation of MMP, all the other types of NS showed conflicting results. Both suppression and induction of MMPs are finally leading to GBM thickening, loss of integrity and proteinuria. Enhanced MMP activity leads to increase in matrix turnover and accumulation of ECM remnants and apoptotic cells leading to fibrosis. On the other hand, diminished expression of MMPs prevents the normal ECM turnover and matrix accumulation. The review compiled the mechanisms of action of both downregulation and upregulation of MMPs. Conclusions: Imbalance of ECM metabolism due to varied expression levels and activities of MMPs in different types of primary NS might contribute to the progression of nephropathies. Further studies are required to identify the potential and usage of MMPs as a diagnostic/prognostic/ therapeutic tool.